The Prognostic Value of Estrogen Receptor β Isoform With Correlation of Estrogen Receptor α Among Sudanese Breast Cancer Patients - Shalabi, Manar G (Breast Cancer (Auckl), 2021)
Two estrogen receptor isoforms (ERα and ERβ) have been characterized with variable and sometimes contrasting responses to estrogens, partially explained by different receptor signaling pathways in estrogen-sensitive tissues. This is a retrospective, descriptive, cross-sectional study, aiming to evaluate the expression pattern of ERβ, employing immunohistochemical techniques using specific monoclonal antibody for ERβ, to correlate its expression with that of ERα in a Sudanese population. Two-hundred and fifty formalin-fixed paraffin-wax-embedded breast tissue blocks were used in this study. Of these, 200 were taken from breast cancer patients ascertained as study cases, and the remaining 50 were noninvolved surgical margin considered as normal breast tissue. Receptor expression was demonstrated using immunohistochemical techniques. The immune expression of ERβ was detected in 57.5% of breast cancers. It was differentially expressed in breast tissues encompassing normal, noninvasive, as well as invasive carcinoma (P = .02). There was no evidence of a significant relationship between ERβ and ERα expression. Among the ERα-negative tumor, 60.4% expressed ERβ. The expression of ERβ among this subgroup was significantly associated with good clinicopathological parameters such as negative Her2/neu, lower grade, and negative lymph node metastasis (P = .002). This study concludes that ERβ was commonly expressed among Sudanese patients with breast cancer, either co-expressed with ERα or expressed alone. In the ERα-negative subgroup, it was associated with better tumor outcomes suggesting ERβ should be included in the diagnostic protocol as an independent marker for favorable prognosis.